Floristic composition, diversity and structure of Khaya senegalensis stands in Benue Department, Cameroon (Journal of Tropical Resources and Sustainable Science (JTRSS), 2020)
The present work has been done to provide basic data for a better conservation and valorization of Khaya senegalensis stands in Sudano-Sahelian zone of Cameroon. A 100 m x 50 m transect method was undertaken to measure floristic diversity through the use of species richness, Shannon index, Pielou equitability, Simpson index, importance value index and importance value family. The vegetation structure is determined by density, basal area and biovolume. The inventory included trees with a dbh ?10 cm on an area of 1 ha per plot. A total of 6743 individuals distributed in 24 families, 33 genera and 54 species were inventoried in all Khaya senegalensis stands studied. Statistical analysis showed significant differences, Shannon index, Simpson index, Pielou equitability, density, basal area, biovolume, species richness, heights class, diameters class, circumferences class but does not certify a significant difference of importance value index among in the villages. The undergrowth of Khaya senegalensis stands is more diverse at Bamé with a Shannon diversity index (ISH=5.87 ± 0.12 bit). The greatest of Pielou equitability is observed at Bamé (EQ=0.80 ± 0.01). The largest of Simpson index is recorded at Bamé (D=0.098 ± 0.001). Khaya senegalensis Stands are denser at Bamé (194 ± 3.12 individuals/ha). The basal area and biovolume of Khaya senegalensis stands are very high at Bamé (BA=25.87 ± 0.06 m2/ha and Biovolume =15.32 ± 0.012 m3/ha). The species importance value is maximal in all the studied villages (SIV=300 ± 71.45). The importance value index of species revealed a clear dominance in the undergrowth of Khaya senegalensis stands are Combretum adenogonium; Acacia senegal; Terminalia laxiflora; Guiera senegalensis; Acacia nilotica; Entada Africana. The vertical structure has three aspects, like the L (Dbh), asymmetric (height) and dissymmetrical (circumference) structures attesting to a strong regeneration of the understory ligneous woods of Khaya senegalensis stands studied.
Keywords: Cameroon; diversity; floristic composition; Khaya senegalensis; structure.; Cameroon; diversity; floristic composition; Khaya senegalensis; structure